2014
DOI: 10.12678/1089-313x.18.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Combined Triaxial Accelerometry and Heart Rate Telemetry for the Physiological Characterization of Latin Dance in Non-Professional Adults

Abstract: The purpose of this study was to value calibrate, cross-validate, and determine the reliability of a combined triaxial accelerometry and heart rate telemetry technique for characterizing the physiological and physical activity parameters of Latin dance. Twenty-two non-professional adult Latin dancers attended two laboratory-based dance trials each. After familiarization and a standardized warm-up, a multi-stage (3 x 5-minute) incremental (based on song tempo) Afro-Cuban salsa choreography was performed while f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 24 publications
1
28
0
1
Order By: Relevance
“…However, Otto et al 57 compared the energy cost of several Zumba dance styles in young healthy women, and found lower HR, oxygen consumption (VO 2 ) and calorie expenditure during Cumbia compared to Salsa (150 vs. 146 beats min −1 , 25.9 vs 22.7 ml kg −1 min −1 , and 7.4 vs 6.6 kcal min −1 ). These differences could be attributed to the high step frequency usually experienced in Salsa (about 120 steps min −1 ), 58 and the different rhythmic structures of these dance styles, with salsa more complex (2/3 rhytmic structure) than Cumbia (simpler binary 2/4 structure). Despite the accelerometers being worn on the wrist in our study, it has been demonstrated that this method is valid to characterise activity levels during a variety of physical tasks involving both upper and lower limbs.…”
Section: Exercise Intensity During the Interventionmentioning
confidence: 99%
“…However, Otto et al 57 compared the energy cost of several Zumba dance styles in young healthy women, and found lower HR, oxygen consumption (VO 2 ) and calorie expenditure during Cumbia compared to Salsa (150 vs. 146 beats min −1 , 25.9 vs 22.7 ml kg −1 min −1 , and 7.4 vs 6.6 kcal min −1 ). These differences could be attributed to the high step frequency usually experienced in Salsa (about 120 steps min −1 ), 58 and the different rhythmic structures of these dance styles, with salsa more complex (2/3 rhytmic structure) than Cumbia (simpler binary 2/4 structure). Despite the accelerometers being worn on the wrist in our study, it has been demonstrated that this method is valid to characterise activity levels during a variety of physical tasks involving both upper and lower limbs.…”
Section: Exercise Intensity During the Interventionmentioning
confidence: 99%
“…Moreover, the control of the autonomic nervous system over HR is a dynamic regulation process (Fisher, Young & Fadel, 2015;Dong, 2016;Chen et al, 2017). Much previous research has also indicated a close linear correlation between HR and VO 2 which is why changes in HR can be used to evaluate exercise intensity (Strath et al 2001;Bouchard & Trudeau 2008;Villars et al 2012;Domene & Easton, 2014;Rousset et al 2015;Colosio et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…The ActiGraph GT3X + accelerometers (ActiGraph, Pensacola, FL, USA) will be used to provide an objective measure of the amount of using the affected arm in the patients’ real-life environments [ 43 ]. The participants will wear the accelerometers on each wrist for three consecutive days before and after treatment.…”
Section: Methodsmentioning
confidence: 99%